Sistema de bioclimatización de viviendas unifamiliares - Nuñez Gavilanez, Katherine Galuth (2022)
Bioclimatic systems seek an integration between architectural and engineering aspects with the environment that surrounds a building. The problem that Ecuador has is the lack of bioclimatic criteria in housing projects of social interest, where there is a focus of interest in addressing the quantitative deficit rather than the qualitative one. For these reasons, this project presents a practical case to implement bioclimatic criteria for application in the city of Babahoyo, Province of Los Ríos. A methodology focused on the Givoni bioclimatic chart was developed, worldwide projects were studied to compile a compilation of the main bioclimatic aspects. Climatological information was collected from the available yearbooks and the strategies applicable to the city of Babahoyo were selected..…..